Various Approaches to Understanding Religion - Marhanah, Ina; Nahari, Lufti; Suparman, Suparman (Al-kayyis: Journal of Islamic Education, 2025)
There are many approaches to understanding religion. This is necessary because these approaches enable believers to experience the functional presence of religion. Without knowledge of these various approaches, it is possible that religion will become difficult for non-functional communities to understand, and ultimately these communities will seek solutions to their problems outside of religion, which should not happen. These approaches include theological-normative, anthropological, sociological, philosophical, historical, cultural, and psychological approaches. This research aims to strengthen beliefs by referring to authoritative sources such as the Qur'an, Hadith, ijma, and qiyas; the research was conducted through literature and text studies, producing a solid doctrinal foundation but one that is prone to exclusivity. Therefore, it needs to be combined with other approaches to be more contextually inclusive. This research employs a qualitative method focused on practices and symbols in daily life. Data sources are collected through field observations and interviews. This approach fosters a rich understanding of religious cultural expressions and promotes an inclusive attitude toward the diversity of religious practices. The results indicate that religion plays a role in strengthening collective solidarity and social mobilization. The implications support the development of adaptive religion-based social policies.